Current trends in aortic valve replacement: development of the rapid deployment EDWARDS INTUITY valve system. (July 2013) - Borger, Michael A; Dohmen, Pascal; Misfeld, Martin; Mohr, Friedrich W
Although conventional aortic valve replacement (AVR) surgery remains the gold standard for patients with aortic stenosis, transcutaneous aortic valve replacement is becoming increasingly common in high-risk patients. The techniques of minimal invasive surgery (MIS) have been well known for many years, but MIS is applied in a disappointingly low percentage of patients undergoing AVR surgery. The EDWARDS INTUITY rapid deployment aortic valve system is designed to facilitate the performance of MIS AVR surgery. In addition, the reduced implantation times may be beneficial in higher risk patients or those requiring concomitant procedures. The system combines established pericardial valve technology with modern stent expertise obtained from the transcutaneous aortic valve replacement experience. Preliminary results from a multicenter trial have shown low rates of morbidity and mortality, and excellent hemodynamic performance. The EDWARDS INTUITY promises to be an exciting device that may further change the landscape of aortic valve intervention.